Pengaruh E-Payment, Literasi Keuangan Syariah dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa Dalam Perspektif Ekonomi Islam - Nur Aeni, Ika; Enggrani Fitri, Lucky; Roihan, Mohammad (ILTIZAM Journal of Shariah Economics Research, 2024)
This study aims to determine the effect of e-payment, Islamic financial literacy and lifestyle on consumptive behavior among students. This research was conducted at the Faculty of Economics and Business, Jambi University. The method used in this research is quantitative method. The technique used in sampling is purposive samling technique. The number of samples taken was 97 respondents from a population of 3,642. Data collection in this study was carried out using a questionnaire. The data analysis technique in this study was carried out using the SmartPLS 3 application program. The results showed that partially e-payment (X1) had no significant effect on consumptive behavior with a statistical T value of 9.240> 1.96 with a significant level (P-value) of 0.000 <0.05. Meanwhile, Islamic financial literacy (X2) has no significant effect on consumptive behavior with a statistical T value of 0.006 < 1.96 with a significant level (P-value) of 0.497 > 0.05 and lifestyle (X3) has a significant effect on consumptive behavior with a statistical T value of 0.091 < 1.96 with a significant level (P-value) of 0.464 > 0.05. Simultaneously e-payment, Islamic financial literacy and lifestylepositively affect consumptive behavior.